Respiratory Muscle Strength Training. - Sapienza, Christine M.; Hoffman, Bari. (San Diego : Plural Publishing, Incorporated, 2020)
Respiratory Muscle Strength Training is a clinical guide, intended to provide clinicians with the background information they need to understand respiratory muscle strength training (RMST). With a variety of case studies provided by well-known authors and clinicians, this text acts as a guidebook to the RMST protocol and provides practical information for use in the field of healthcare. In addition to real-world case studies, Respiratory Muscle Strength Training includes a chapter devoted to Frequently Asked Questions, a representative sample of the devices commonly used for respiratory traini.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Respiratory organs -- Diseases -- Patients -- Rehabilitation; Respiratory organs -- Diseases -- Treatment; Respiratory muscles -- Physiology; Breathing exercises; Breathing Exercises -- methods; Respiratory Muscles -- physiology; Muscle Strength; Respiration Disorders -- therapy; Breathing Exercises; Handicapés respiratoires -- Réadaptation.; Appareil respiratoire -- Maladies -- Traitement; Appareil respiratoire -- Muscles -- Physiologie; Exercices respiratoires; Respiratory muscles -- Physiology; Respiratory organs -- Diseases -- Patients -- Rehabilitation; Respiratory organs -- Diseases -- Treatment